2017
DOI: 10.5194/gmd-2017-136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 4.5 km resolution Arctic Ocean simulation with the global multi-resolution model FESOM1.4

Abstract: Abstract. In the framework of developing a global modeling system which can facilitate modeling studies on Arctic Ocean and high-mid latitude linkage, we evaluate the Arctic Ocean simulated by the multi-resolution ocean sea-ice model FESOM.To explore the value of using high horizontal resolution for Arctic Ocean modeling, we use two global meshes differing in Atlantic Water (AW) mean state and variability. The deepening and thickening bias of the AW layer, a common issue found in coarse resolution simulations,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Increasing ocean model resolution in ocean models has a critical impact on the role that eddies play in the ocean heat budget and in the dynamics of major frontal systems (see, e.g., Iovino et al, ; Von Storch et al, ). Enhanced resolution improves the representation of narrow boundary currents (e.g., Marzocchi et al, ; Sein et al, ; Wang et al, ) and the connectivity between ocean basins (e.g., Chang et al, ). Increases of resolution in atmosphere‐only models have also beneficial impacts on many aspects of the large‐scale circulation and lead to a more realistic simulation of regional climate and small‐scale phenomena (Jung et al, , and Haarsma et al, , for a comprehensive review).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing ocean model resolution in ocean models has a critical impact on the role that eddies play in the ocean heat budget and in the dynamics of major frontal systems (see, e.g., Iovino et al, ; Von Storch et al, ). Enhanced resolution improves the representation of narrow boundary currents (e.g., Marzocchi et al, ; Sein et al, ; Wang et al, ) and the connectivity between ocean basins (e.g., Chang et al, ). Increases of resolution in atmosphere‐only models have also beneficial impacts on many aspects of the large‐scale circulation and lead to a more realistic simulation of regional climate and small‐scale phenomena (Jung et al, , and Haarsma et al, , for a comprehensive review).…”
Section: Introductionmentioning
confidence: 99%
“…According to Jahn et al (2012) the highest inter-model agreement is found for the interannual and seasonal variability of the solid freshwater export and the solid freshwater storage, which also agree well with observations. In particular, Wang et al (2017) suggested that the spread on the freshwater export from the Arctic towards the Atlantic might be a result of the different representations of the straits (width, depth and grid spacing) and numerical schemes (e.g., momentum advection and boundary conditions). Although Wang et al (2017) did not attribute a one way response to model resolution, they found that increased horizontal ocean model resolution does not necessarily lead to liquid freshwater fluxes comparable with observations.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we use a mesh with a 4.5‐km horizontal grid spacing (defined as the length of the triangle sides) in the Arctic Ocean and an equivalent of 1° resolution in the rest of the globe (Wang, Wekerle, Danilov, Wang, et al, ). The mesh has 47 unevenly spaced vertical layers.…”
Section: Model Description and Methodsmentioning
confidence: 99%
“…Most of the model parameters in our runs are the same as those of Wang, Wekerle, Danilov, Wang, et al (). The transition from FESOM1.4 to FESOM2, however, leads to some modifications in the ocean circulation, which will be reported in a dedicated ocean model evaluation paper.…”
Section: Model Description and Methodsmentioning
confidence: 99%
See 1 more Smart Citation